2016
DOI: 10.1039/c5ra24231b
|View full text |Cite
|
Sign up to set email alerts
|

Simple synthesis process for ZnO sphere-decorated CNT fiber and its electrical, optical, thermal, and mechanical properties

Abstract: An easy process to produce ZnO sphere-decorated CNT (ZSDC) fibers was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…This observation was expected, judging from the fact that the presence of the nanoparticles located on the nanotube surface improves the CNT dispersion in the polymer solution. As expected, the presence of ZnO nanoparticles on MWCNTs improved the mechanical properties due to the chemical reaction formed between nanoparticles with the existing functional groups of individual CNTs [54].…”
Section: Discussionsupporting
confidence: 75%
“…This observation was expected, judging from the fact that the presence of the nanoparticles located on the nanotube surface improves the CNT dispersion in the polymer solution. As expected, the presence of ZnO nanoparticles on MWCNTs improved the mechanical properties due to the chemical reaction formed between nanoparticles with the existing functional groups of individual CNTs [54].…”
Section: Discussionsupporting
confidence: 75%
“…01-075-0576. [34][35][36][37][38] The high-intensity (101)-plane peak at 35.5 indicated that the nanorods were selectively oriented to the (101) plane. The 2-30 (2q) area was magnied and shown in Fig.…”
Section: Zno and Ht Zno Nanorodsmentioning
confidence: 99%
“…It is the characteristic peak of carbon at position 22.75. 37,[39][40][41] This broad band carbon peak suggests that low-crystalline carbon is present in the ZnO nanorods. The formation of low-crystalline carbon inside the ZnO nanorods may have occurred during the decomposition of recrystallized zinc acetate 450 C for 45 min.…”
Section: Zno and Ht Zno Nanorodsmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have attracted significant scientific and technological attention due to their exceptional mechanical12, electrical13, and thermal properties14. Specifically, CNTs are promising candidates for next-generation reinforcement composite materials, which require extraordinarily high strength with low weight and appropriate electrical properties15.…”
mentioning
confidence: 99%